SHAOLIN CULTURAL BRAND UNDER THE BACKGROUND OF THE BELT AND ROAD INITIATIVE - Li, Qinye (Journal of Dharma, 2021)
The 2030 Agenda for Sustainable Development has brought the importance of a sustainable economy to the forefront. Establishing a sustainable development path that conforms to human ethical standards and promotes economic growth has been an urgent issue. The implementation of the Belt and Road Initiative has presented both opportunities and challenges in the external communication of the Shaolin cultural brand. On the one hand, the implementation of the proposal urgently requires external cultural communication; the spread of Buddhism on the ancient Silk Road laid a solid foundation for the external communication of the Shaolin cultural brand. Since China’s reform and opening up, the Shaolin temple has gradually become a face of Chinese culture and has had a strong international influence. However, the lack of shared culture with the countries along the route, the asymmetry of the discourse system, and the imperfect support mechanism for external communication make the external communication of Shaolin cultural brand face cultural discounts. Based on the research on the development and dissemination of Shaolin cultural industry under the background of the ‘Belt and Road Initiative,’ this article attempts to explore a new path for sustainable economic and cultural development in the 21st century and promote the maintenance of the cultural diversity of the world, the breaking of the self-centred thinking paradigm, and the construction of a Community with a Shared Future for Humanity.